Research on the impact of equity incentives on the financial performance of new energy enterprises - Chen, Keyu; Yu, Yaguai; Jiang, Pengtao; Bao, Hanlu; Ni, Taohan (Frontiers in Environmental Science, 2023)
Based on the data of 253 A-share listed new energy enterprises from 2010–2021, this paper studies the correlations among equity incentives, the three contract elements of equity incentives and the financial performance of new energy enterprises by using fixed-effect regression analysis, and on this basis, Granger causality analysis is applied to determine the causal relationship, and finally, the degree of influence of equity incentives contract elements is further studied by Grey Relational Analysis. It is found that equity incentives positively affect the financial performance of new energy enterprises as a whole. In terms of the choice of equity incentive contract elements, the influence is more significant when the granting method is stock options, when the exercise duration is longer, and when the exercise conditions are stricter. As to the degree of influence, the influence of equity incentive method and exercise conditions on the financial performance of new energy enterprises is greater, but the influence of exercise duration is the lowest. Therefore, it is suggested that new energy enterprises can choose more stock options for equity incentives, create stricter exercise conditions and set the duration of the equity incentive scheme between 5 and 10 years with their own characteristics.